Etapy i osnovnye pokazateli raboty laboratorii biomekhanika VNIIFKa - Ratov, I. P.; Popov, G. I. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The aim of this paper was to analyze the history of the VNIIFK`s biomechanics laboratory in connection with the development of the world famous scientific school having been created their by I. P. Ratov.